Pengolahan Kacang Merah Bagi Siswa SMK Negeri 1 Bawen Kapubaten Semarang - Aldila Sagitaning Putri; Dewi Larasati; Elly Yuniarti Sani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Red beans (Phaseolus vulgaris L.) are a type of legumes (Leguminaceae) that have a high content of starch and fiber. The high fiber content causes red beans to prevent coronary heart disease. Red beans also have a low glycemic index so they can lower cholesterol levels in the blood and the risk of diabetes. Red beans also contain phenolic compounds that act as antioxidants in the body. Red beans are classified as food ingredients that can support the increase in nutritional value because they are classified as a relatively affordable source of vegetable protein. The purpose of this counseling is to provide knowledge and processed skills from local commodities, in this case red beans, to students majoring in Agribusiness of Agricultural Products at SMK Negeri 1 Bawen. This activity was attended by 68 students majoring in Agribusiness and Agricultural Products and 1 assistant teacher from SMK Negeri 1 Bawen, Semarang Regency. The method of this red bean processing extension activity is to increase the knowledge and skills of making processed local food products with several methods: a. The lecture method provides the theory and practice of making kidney bean cookies. b. Practice method of making red bean cut ice. c. The question and answer method, used to provide feedback to participants about the material that has been presented during the activity. d. Evaluation is given by providing pre test and post test. After the implementation, it showed that the target, namely students of SMK Negeri 1 Bawen, increased their knowledge and understood the importance of post-harvest handling and processing of red beans with the practice of making red bean cut ice. This is based on questions and answers, interviews and questionnaires shared before and after the activity. From the results of the questionnaire conducted before and after the activity, it showed that: After the implementation, there was a 50.17% increase in knowledge about kidney bean processing, Knowledge about making kidney beans into cut ice increased by 65.32% and Knowledge of other processed kidney beans such as kidney bean cookies showed that there was an increase of 67.15% after counseling. The conclusions that can be drawn from this counseling activity are (1) Processed red bean extension activities can increase the knowledge and understanding of the participants (2) The responses given by the counseling participants show a fairly satisfactory interest and there is a desire to apply the newly acquired knowledge to be socialized in the surrounding environment.